Lateral Dynamic Response of a Single Pile Model - Norazzlina, M.Sa‘don; Pender, M.J.; Orense, R.P; Abdul Razak, Abdul Karim (2008)
The dynamic response of a single pile with an attached mass giving a single degree of freedom (SDOF) system subjected to lateral pile-head loading is described. Two types of dynamic tests were performed, primarily free-vibration and dynamic forced-vibration tests. The main aims of this paper were to provide a basic understanding of the single pile head action and to evaluate the applicability of the elastic continuum method (ECM) in estimating the dynamic parameters of the pile-soil system. The single pile model was constructed using an instrumented steel pipe with an outside diameter of 50.65 mm and a wall thickness of 1.05 mm. The measured data from the frequency domain analysis were analysed to determine the natural frequencies fn, damping ratios ζ, and lateral pile-mass connection displacement uLat of the pile-soil system. The experimental results obtained were then compared with those calculated from the analytical calculation based on the ECM. The analytical prediction was based on a perfect pile-soil bonding with the pile embedded in a homogeneous soil layer with a constant Young’s modulus with depth. The natural frequency obtained from the free-vibration test was greater than that from forced-vibration test. This was found to be in general agreement with other related published works. The experimental and analytical results were shown to be reasonably matched, thus, the ECM demonstrates a good potential application in estimating the dynamic parameters and the lateral displacement.